Zn (NDIH) film and anodized aluminum oxide photonic crystal and application of Zn (NDIH) film and anodized aluminum oxide photonic crystal as electrochromic material

By combining Zn(NDI-H) film with anodized aluminum photonic crystals to form an electrochromic material, the problem of multi-background fusion invisible materials in the prior art is solved, and the collaborative color rendering effect of multiple colors is achieved.

CN119717347AActive Publication Date: 2025-03-28NANJING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311277878.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The prior art is difficult to achieve multi-background fusion stealth materials in the visible light band, especially in the combination of electrochromic coordination polymers and photonic crystals, and precise color regulation is still a major problem.

Method used

An electrochromic material composed of Zn(NDI-H) film and anodized aluminum photonic crystal is used to grow Zn(NDI-H) film on the FTO conductive surface and to bond with anodized aluminum photonic crystal, and a conductive liquid is added between the two to achieve collaborative color development.

Benefits of technology

The collaborative color development of Zn(NDI-H) film and anodized aluminum photonic crystal is achieved. When a voltage is applied, the color of the material can change from earth yellow to light yellow, and then to light green, solving the limitations of single color change.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119717347A_ABST
    Figure CN119717347A_ABST
Patent Text Reader

Abstract

The invention discloses a Zn (NDIH) thin film coated anodic aluminum oxide photonic crystal and application of the Zn (NDIH) thin film coated anodic aluminum oxide photonic crystal as an electrochromic material. The electrochromic material is composed of a Zn (NDI-H) thin film and an anodic aluminum oxide photonic crystal, the Zn (NDI-H) thin film grows on the FTO conductive surface, the Zn (NDI-H) thin film and the anodic aluminum oxide photonic crystal are arranged in an attached mode, conductive liquid is arranged between the Zn (NDI-H) thin film and the anodic aluminum oxide photonic crystal, and the structural color of the anodic aluminum oxide photonic crystal is earthy yellow. Voltage is applied to the two ends of the Zn (NDI-H) film and the anodized aluminum oxide photonic crystal, the Zn (NDI-H) film and the anodized aluminum oxide photonic crystal achieve collaborative color development, and when the voltage is switched from-4.5 V to-5.5 V, the whole device changes from faint yellow to faint green.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of electrochromic materials, and in particular relates to the use of a Zn (NDI-H) film and anodized aluminum photonic crystal color-changing material. Background Art

[0002] The traditional means of stealth in the visible light band is to apply camouflage that matches the background color on the physical surface, thereby minimizing the visual contrast characteristics such as brightness and chromaticity between the target and the background. Although this method is easy to implement, it can only show a good stealth effect when the target is stationary or moving slowly, and the color resolution is low, which makes it easy to be discovered and tracked by modern high-resolution detectors. Therefore, it is of great significance to develop intelligent stealth color-changing materials that can actively blend into the background according to background changes, especially typical background changes such as forests, deserts and shallows.

[0003] Photonic crystals are artificial microstructures formed by periodic arrangement of dielectric materials and materials with different refractive indices as basic units. The photonic band gap can be adjusted by fine-tuning the structure, and then the color of the material can be adjusted. Flexible coordination polymers are a type of material that is connected to organic ligands through a certain topological structure with metals (or metal clusters) as nodes and has certain flexibility and potential porosity. Due to the diversity of coordination modes, flexibility in ligand design, and adjustability of electrical properties, coordination polymers have shown superior performance in the field of electrochromism. However, most of the current reports on photonic crystals in the visible light band multi-background fusion stealth materials and technologies are in the early stages of theoretical and experimental exploration. How to combine electrochromic coordination polymers with photonic crystals is a problem. People have not fully understood the mechanism of synergistic color change between electrochromic coordination polymers and photonic crystals, and the precise control of their color is still a big problem. Summary of the invention

[0004] In order to overcome the problem of single color change of Zn(NDI-H), the present invention provides a Zn(NDI-H) film@anodized aluminum oxide photonic crystal and its application in electrochromism.

[0005] The technical solution to achieve the purpose of the present invention is: a Zn (NDI-H) film @ anodized aluminum photonic crystal, the electrochromic material is composed of a Zn (NDI-H) film and anodized aluminum photonic crystals, the Zn (NDI-H) film is grown on the FTO conductive surface, the Zn (NDI-H) film and the anodized aluminum photonic crystal are bonded together, a conductive liquid is arranged between the two, and the structural color of the anodized aluminum photonic crystal is khaki.

[0006] Preferably, the conductive liquid is a DMF solution of TBA·PF6 with a concentration of 0.1 M.

[0007] Preferably, the Zn(NDI-H) film and the anodized aluminum photonic crystal are attached to each other by external force.

[0008] The method for preparing the above-mentioned Zn(NDI-H) film@anodized aluminum oxide photonic crystal comprises the following steps: Step 1: Ultrasonic cleaning and electrochemical polishing of the aluminum sheet; Step 2: using the aluminum sheet obtained in step 1 to prepare an anodized aluminum photonic crystal with a yellowish structural color by using a periodic current changing method; Step 3: Dissolve the ligand H2NDI-H and Zn(NO3)2·6H2O in DMF, place vertically on the FTO substrate, slowly heat to 130 °C for about 30 minutes, and stand at 130 °C for a while; Step 4: After the reaction is completed, the substrate is taken out, immersed in DMF for ultrasonic treatment to remove loose powder, and then the film on the non-conductive surface of the substrate is wiped off to obtain a Zn (NDI-H) film grown on the conductive surface of FTO; Step 5: Add an appropriate amount of conductive liquid on the surface of the anodized aluminum photonic crystal, and then use external force to fit the Zn (NDI-H) film grown on the FTO conductive surface to the anodized aluminum photonic crystal, wherein the Zn (NDI-H) film is in contact with the anodized aluminum photonic crystal.

[0009] Preferably, in step 1, the electrochemical polishing voltage is 21 V; and the electrochemical polishing temperature is 0-5 °C.

[0010] Preferably, in step 2, when the anodized aluminum oxide photonic crystal is prepared by the periodic variable current method, the waveform of the periodic current density is: within one cycle of 1100 seconds, t 1 The time current density is j 1 =1.12 mA / cm 2 , t 2 The time current density is j 2 =0.28 mA / cm 2 , t 1 and t 2 The ratio is 1:4; the number of cycles is 145, the oxidation time of the last cycle is 85% of the first cycle, and the oxidation time of each cycle decreases by 0.1%; the electrolyte is 0.5 M sulfuric acid; the electrolysis (oxidation) temperature is 0~5℃.

[0011] Preferably, in step 3, the size of the FTO substrate is 2×1 cm 2 .

[0012] Preferably, in step 3, the mixture is allowed to stand at 130° C. for 3 to 4 hours.

[0013] The above-mentioned Zn(NDI-H) film @ anodized aluminum photonic crystal is used as an electrochromic material. A voltage of 0~-5.5 V is applied across the Zn(NDI-H) film @ anodized aluminum photonic crystal. When the voltage is switched from 0 V to -4.5 V, the material changes color from the structural color (khaki) of the anodized aluminum photonic crystal itself to light yellow; when the voltage is switched from -4.5 V to -5.5 V, the material changes color from light yellow to light green.

[0014] Compared with the prior art, the advantages of the present invention are: (1) Zn (NDI-H) film @ anodized aluminum photonic crystal is used for the first time as an electrochromic material, which is composed of a Zn (NDI-H) film and anodized aluminum photonic crystal. The Zn (NDI-H) film is grown on a FTO conductive surface. The Zn (NDI-H) film is in contact with the anodized aluminum photonic crystal, and a conductive liquid is arranged between them. The structural color of the anodized aluminum photonic crystal is khaki.

[0015] (2) When voltage is applied across the Zn(NDI-H) film@anodized aluminum photonic crystal, the Zn(NDI-H) film and the anodized aluminum photonic crystal achieve synergistic color display. When the voltage is switched to -4.5 V, the entire device presents a light yellow-dominated color; when the voltage is switched to -5.5 V, the entire device presents a light green-dominated color. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a physical picture of the khaki anodized aluminum photonic crystal prepared in Example 1.

[0017] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of H2NDI-H prepared in Example 1.

[0018] Figure 3 This is the X-ray diffraction pattern of the Zn(NDI-H) thin film on the FTO substrate described in Example 1.

[0019] Figure 4 The color change of the Zn(NDI-H) film in the conductive liquid described in Example 1 with voltage.

[0020] Figure 5 This is the cyclic voltammogram of the Zn(NDI-H) thin film on the FTO substrate described in Example 1 (25 cycles).

[0021] Figure 6The color change of the FTO / Zn(NDI-H) film / FTO sandwich structure described in Example 1 with voltage.

[0022] Figure 7 The synergistic color change of the FTO / Zn(NDI-H) film / conductive solution / anodized aluminum photonic crystal sandwich structure described in Example 1 with voltage. DETAILED DESCRIPTION

[0023] The present invention will now be further described with reference to the embodiments and the accompanying drawings: The inventor originally planned to grow a layer of Zn (NDI-H) film directly on the anodized aluminum photonic crystal, so that the Zn (NDI-H) film and the anodized aluminum photonic crystal are integrated, and voltage is applied to study their synergistic color change behavior. However, during the experiment, it was found that after the Zn (NDI-H) film and the anodized aluminum photonic crystal were integrated, due to the presence of the aluminum substrate, the current did not flow through the Zn (NDI-H) film, and the synergistic color development caused by electrochromism could not be achieved. Therefore, the strategy was changed, and a FTO / Zn (NDI-H) film / conductive solution / anodized aluminum photonic crystal sandwich structure was constructed, and voltage was applied to make it have synergistic color change behavior. Example 1

[0024] The aluminum sheet with a purity of 99.99% was ultrasonically cleaned in acetone and anhydrous ethanol solution for 5 min to remove oil stains. The aluminum sheet was electrochemically polished at 0-5 ℃ using ethanol / perchloric acid solution with a volume ratio of 4:1 as the polishing solution, and the polishing voltage was 21 V. At 0-5 ℃, in 0.5 M sulfuric acid electrolyte, 1.12 mA / cm 2 After 2 h of current density oxidation, the aluminum sheet was oxidized with a periodic current. The waveform of the periodic current density is: In one cycle, t 1 The time current density is j 1 =1.12mA / cm 2 , t 2 The time current density is j 2 =0.28 mA / cm 2 , t 1 and t 2The ratio is 1:4. Anodized aluminum photonic crystals were obtained by anodizing for 145 cycles. During the anodizing process, a gradual compensation measure was used to control the bandgap drift. The specific method was that the oxidation cycle time was not a fixed value, but gradually decreased. The oxidation time of the last cycle was 85% of the first cycle, that is, the oxidation time of each cycle decreased by 0.1%. The anodized aluminum photonic crystal with a structural color of khaki was obtained by using this periodic variable current method, such as Figure 1 shown.

[0025] In a dry 100 ml flask, add 0.86 g of 1,4,5,8-naphthalenetetracarboxylic anhydride, 0.75 g of 3,5-dimethyl-1H-pyrazol-4-amine and 50 ml of anhydrous DMF. Heat the reaction mixture at 150 °C under nitrogen and stir rapidly for 12 hours. After the reaction, cool the flask to room temperature and pour the solution in the flask into 150 ml of stirred ether. Filter and separate the precipitated solid, and recrystallize it from DMF / ether / H2O (10 ml:15 ml:5 ml). Filter the product and dry it in vacuum at 70 °C to obtain H2NDI-H, whose hydrogen nuclear magnetic resonance spectrum is as follows: Figure 2 shown.

[0026] In a 100 ml screw-top jar, 118 mg of the ligand H2NDI-H and 86 mg of Zn(NO3)2·6H2O were dissolved in 60 ml of DMF. 2 The FTO substrate was placed in a screw-top jar and immersed below the surface of the solution. The screw-top jar was immersed in an oil hot bath and slowly heated to 130 °C under a nitrogen atmosphere for about 30 minutes and maintained at this temperature for 3.5 hours. After the reaction was completed, the mixture was cooled to room temperature, the substrate was removed, and the substrate was washed with acetone to remove loose powder. Immersed in a vial containing 20 ml of DMF, the vial was ultrasonically treated for about 1 minute. After ultrasonic treatment, the film was washed with acetone to remove residual powder. The substrate was taken out and the film attached to the non-conductive surface of the FTO plate was carefully wiped with a cotton swab moistened with 1 M HCl solution (before spectroelectrochemical measurement). After washing with ethanol and acetone and vacuum drying at 70 °C, the Zn(NDI-H) electrochromic film was prepared on the FTO conductive substrate, and its X-ray diffraction pattern is shown in the figure. Figure 3 Shown In DMF solution containing 0.1 M TBA·PF6, FTO film was used as the working electrode, platinum mesh was used as the counter electrode, and Ag / Ag (acetonitrile) + Cyclic voltammetry (CV) measurements were performed as a reference electrode. During the cycling process, the Zn(NDI-H) film changed from nearly transparent colorless to light yellow and then to dark brown. The color change was rapid and reversible. Figure 4It is noteworthy that the Zn(NDI-H) film also exhibits excellent electrochemical cycling stability, with no decrease in the peak current observed over 25 cycles at a scan rate of 100 mV / s, as shown in Figure 2. Figure 5 shown.

[0027] A FTO / Zn(NDI-H) film / FTO sandwich structure was constructed, with the FTO / Zn(NDI-H) film as the working electrode and the blank FTO as the counter electrode. A drop of 0.1 M TBA·PF6 DMF solution was added to the blank FTO as a conductive liquid, and then the FTO / Zn(NDI-H) film was covered and clamped so that the Zn(NDI-H) film was in contact with the blank FTO. When the voltage was switched from 0 V to -2.7 V, the device changed from a nearly transparent and colorless state to a light yellow state; when the voltage was switched from -2.7 V to -3.0 V, the device showed a dark brown color, as shown in Figure 2. Figure 6 shown.

[0028] A FTO / Zn(NDI-H) film / conductive solution / anodized aluminum photonic crystal sandwich structure was constructed, with the FTO / Zn(NDI-H) film as the working electrode and the anodized aluminum photonic crystal as the counter electrode. A drop of 0.1 M TBA·PF6 DMF solution was added to the anodized aluminum photonic crystal as the conductive liquid, and then the FTO / Zn(NDI-H) film was covered and clamped so that the Zn(NDI-H) film was in contact with the anodized aluminum photonic crystal. At 0 V, the Zn(NDI-H) film was transparent, and the entire device showed the structural color of the anodized aluminum photonic crystal itself; when the power was turned on, the Zn(NDI-H) film and the anodized aluminum photonic crystal achieved synergistic color display. When the voltage was switched to -4.5 V, the entire device showed a light yellow-dominated color; when the voltage was switched to -5.5 V, the entire device showed a light green-dominated color, such as Figure 7 shown.

[0029] The above implementation results show that it is feasible to use a single coordination polymer for electrochromic change. Zn(NDI-H) has the advantages of good redox reversibility and high porosity, but the single color change limits its application in the electrochromic direction.

Claims

1. A Zn(NDI-H) film@anodized aluminum photonic crystal, characterized in that: The electrochromic material consists of a Zn (NDI-H) film and anodized aluminum photonic crystals. The Zn (NDI-H) film is grown on a conductive surface of FTO. The Zn (NDI-H) film and the anodized aluminum photonic crystals are bonded together, and a conductive liquid is arranged between the two. The structural color of the anodized aluminum photonic crystals is khaki.

2. The Zn(NDI-H) film@anodized aluminum oxide photonic crystal according to claim 1, characterized in that: The conductive liquid was a 0.1 M TBA·PF6 solution in DMF.

3. The Zn(NDI-H) film@anodized aluminum oxide photonic crystal according to claim 1, characterized in that: The Zn(NDI-H) film and the anodized aluminum photonic crystal are attached to each other by external force.

4. A method for preparing Zn(NDI-H) film@anodized aluminum oxide photonic crystal, characterized in that: The steps include: Step 1: Ultrasonic cleaning and electrochemical polishing of the aluminum sheet; Step 2: using the aluminum sheet obtained in step 1 to prepare an anodized aluminum photonic crystal with a yellowish structural color by using a periodic current changing method; Step 3: Dissolve the ligand H2NDI-H and Zn(NO3)2·6H2O in DMF, place vertically on the FTO substrate, slowly heat to 130 °C for about 30 minutes, and stand at 130 °C for a while; Step 4: After the reaction is completed, the substrate is taken out, immersed in DMF for ultrasonic treatment to remove loose powder, and then the film on the non-conductive surface of the substrate is wiped off to obtain a Zn (NDI-H) film grown on the conductive surface of FTO; Step 5: Add an appropriate amount of conductive liquid on the surface of the anodized aluminum photonic crystal, and then use external force to fit the Zn (NDI-H) film grown on the FTO conductive surface to the anodized aluminum photonic crystal, wherein the Zn (NDI-H) film is in contact with the anodized aluminum photonic crystal.

5. The method according to claim 4, characterized in that In step 1, the electrochemical polishing voltage is 21 V; the electrochemical polishing temperature is 0~5 ℃.

6. The method according to claim 4, characterized in that In step 2, when the anodized aluminum photonic crystal is prepared by the periodic variable current method, the waveform of the periodic current density is: within one cycle of 1100 seconds, t 1 The time current density is j 1 =1.12 mA / cm 2 , t 2 The time current density is j 2 =0.28 mA / cm 2 , t 1 and t 2 The ratio is 1:4; The number of cycles is 145, the oxidation time of the last cycle is 85% of the first cycle, and the oxidation time of each cycle decreases by 0.1%; The electrolyte is 0.5 M sulfuric acid; the electrolysis (oxidation) temperature is 0~5 ℃.

7. The method according to claim 4, characterized in that In step 3, the size of the FTO substrate is 2×1 cm 2 .

8. The method according to claim 4, characterized in that In step 3, the mixture is allowed to stand at 130°C for 3 to 4 hours.

9. Use of the Zn(NDI-H) film@anodized aluminum oxide photonic crystal as claimed in any one of claims 1 to 3 as an electrochromic material.

10. The use according to claim 9, characterized in that When a voltage is applied across the Zn(NDI-H) film@anodized aluminum photonic crystal and the voltage is switched from -4.5 V to -5.5 V, the color of the material changes from light yellow to light green.

Citation Information

Patent Citations

  • Preparation method of electrochromic film of anodic oxidation TiO2 nanotube array

    CN105036566A

  • Electrochromic photonic crystal film and preparation method and application thereof

    CN113103706A

  • Electrochromic photonic crystal thin films, their preparation methods, and applications

    CN113103706B

  • Preparation method of film electrode for electrochromic device, film electrode and application

    CN114716155A